Changes of structural organization of human olfactory bulbs under conditions of severe forms of pneumonia and cerebrovascular pathology - A.D. Shkodina; R.M. Grinko; I.I. Starchenko; N.I. Vynnyk; S.M. Sovhyria; V.F. Kyslyi (Medičnì Perspektivi, 2021)
The role of human olfactory bulbs remains one of the most interesting questions concerning work of the brain, because this organ is one in which neurogenesis is continuously generated in post-natal and adult periods. Impaired sense of smell is not a pathology that threatens human life, therefore, often remains unnoticed. However, it can directly affect the quality of life, as it leads to malnutrition and certain problems in interpersonal relationships. The study of the functional structure of the olfactory analyzer plays an important role both in clinical and experimental studies, but the question of its features in humans needs detailed research. The material of the research was 18 pairs of the olfactory bulbs of males and females aged from 30 to 90 years that were received at the Poltava Regional Department of Pathology. In order to objectify the data obtained on micropreparations, the following morphometric indices were determined: the specific gravity of the location of cellular elements; the proportion of mitral neurocytes in the entire cell population; percentage ratio of relative quantity between cellular elements, blood microvessels, fibrillar component and homogeneous eosinophilic structures. Correlation analysis of morphometric indices in the general sample revealed the existence of an inverse communication of average strength between the relative number of homogeneous eosinophilic cells and the relative number of cellular elements and blood microvessels, which in turn indicates the etiopathogenetic mechanisms of the formation of these structures. The conducted research makes it possible to conclude that mitral cells as one of the most differentiated in olfactory bulbs are sensitive to the development of hypoxic states; under the conditions of cerebrovascular pathology, the relative amount of the blood vessels of the microvessels decreases, which leads to the disorder of the trophy of the nervous tissue and as a result can lead to neurocytolysis of mitral cells. Changes in the vascular and cellular component indicate a different pathogenesis of changes in human olfactory bulbs in these pathologies and suggest that eosinophilic homogeneous cells are the result of apoptotic neurocytolysis against the background of development of hypoxic states.